KETIDAKSETARAAN PROSES REHABILITASI DAN REINTEGRASI DALAM KASUS PELECEHAN SEKSUAL DI LEMBAGA PEMBINAAN KHUSUS ANAK TENGGARONG - Ahmed Farid; Ivan Zairani Lisi; Nur Aripkah (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study analyzes inequality in the rehabilitation and reintegration of juvenile sexual offenders at LPKA Tenggarong. The study employs a socio-legal approach by combining normative legal analysis with empirical findings obtained through interviews and literature review. The research focuses on the implementation of rehabilitation and reintegration programs as well as the obstacles faced in the process. The results show that rehabilitation programs at LPKA Tenggarong have not been implemented optimally and equally. Existing programs are mainly focused on educational and vocational activities, while psychosocial assistance and psychological counseling remain limited. In addition, weak coordination between correctional institutions, families, schools, and communities hinders the reintegration process. Social stigma and environmental rejection also negatively affect children’s behavioral recovery and adaptation after release, increasing the risk of reoffending. Therefore, improvements in rehabilitation quality, psychosocial support, family involvement, and multisectoral coordination are necessary to support effective social reintegration and prevent repeated criminal behavior.